Synthesis, Screening and QSAR Studies of 3-Benzoyl-2-thioxo-1,2,3,4- tetrahydropyrimidine Analogues as Antibacterial Agents - Sawant, R.L.; Bhatia, M.S. (Asian Journal of Chemistry, 2010)
5-Acyl-6-methyl-4-substituted-2-thioxo-1,2,3,4-tetrahydropyrimidines (1) were synthesized by cycloconden-sation reaction between appropriate aldehyde, acetoacetate and thiourea in presence of aluminium chloride and hydrochloric acid which upon treatment with benzoyl chloride in presence of pyridine in benzene furnish the 3-benzoyl-2-thioxo-1,2,3,4- tetrahydropyrimidine analogues (2a-l). The structures of all these compounds have been confirmed on the basis of their analytical, IR and NMR spectral data. These compounds have also been tested for antibacterial activity against Staphylococcus aureus. A quantitative structure activity relationship study was made using various descriptors. Several statistical expressions were developed using stepwise multiple linear regression analysis. The best quantitative structure activity relationship model was further cross validated. The study revealed that electronic property (AM1_LUMO) and lipophilic descriptor (BCUT_SLOGP_1) both contributes negatively which suggest that minimizing both the Lowest Unoccupied Molecular Orbital energy and atomic contribution to partition coefficient (log P) may lead to better antibacterial compound from this series.